Student’s Acquisition of Global Education Perspectives in Social Studies - Tuazon, Ariel; Claveria, Janice (Social Sciences and Development Review, 2015)
The world is interdependent. The survival and well-being of a country is intimately related to its ability to deal effectively with other people and nations. With a host of international issues, global studies can be viewed as basic education. In this regard, the study aimed to determine how the promotion of global education in Social Studies impacts on students’ acquisition of global perspectives in the public secondary schools in the DepEd Division of Batangas City. Three hundred fifty-four students participated in the investigation. Results of the study showed that promotion of global education is significantly related to students’ acquisition of global perspectives. The teachers amply integrated global education in their lessons and that their students possessed global perspectives. Global education was regarded as an inherent and important component of the Social Studies curriculum. The discussion of world problems, issues and concerns enabled students to develop virtues of empathy, responsibility and civic mindedness making them global citizens beyond national boundary. The subject Social Studies sufficiently provided a setting for the students to develop global perspectives.
Keywords: social studies; public secondary school; global education; perspectives in high school curriculum; global perspectives